ANALISIS YURIDIS TERHADAP PENYANGKALAN TANDA TANGAN DALAM AKTA JUAL BELI DI HADAPAN PEJABAT PEMBUAT AKTA TANAH (PPAT) (STUDI PUTUSAN MAHKAMAH AGUNG NO. 1175 K/PID/2016) - FITRI FITRI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Syafruddin Kalo, SH, MHum2. Notaris Dr. Suprayitno, SH, MKn3. Notaris Dr. Henry Sinaga, SH, MKn The Implementation of PP No. 24/1997 on Land Registration, concerning AJB, in its closing remark, states that the Deed is signed by or affixed with thumbprints of the persons appearing, witnesses, and PPAT. The research used juridical normative and descriptive analytic method. Repudiation of signatures in the AJB is caused by some factors such as the persons appearing do not come, they do not receive the money of the transaction, or they do not sign the AJB. The Supreme Curt’s Ruling No. 1175 K/Pid/2016 on 1 year and 8 month-imprisonment is handed down based on the evidence of authentic Deed forgery according to Article 264 of the Penal Code in conjunction with Article 55 of Penal Code. He should not do in his Deed which serves one’s own purposes and harms other parties. Besides signing AJB, the persons appearing should also give the thumbprints to avoid signature repudiation. He should increase his service quality and equip his office facility with audio-visual, photographs, and CCTVs.Keywords: Repudiation, Signature, Sales Certificate, PPAT (Official Empowered to Draw up Land